All-solid-state battery and preparation method thereof
The electrolyte powder is crushed and mixed by acoustic resonance method to form a modified electrode and prepare a separator, which solves the problem of low efficiency in the production process of solid-state batteries and achieves efficient preparation of all-solid-state batteries.
Patent Information
- Application Number
- CN202510177518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-18
AI Technical Summary
In the prior art, the production process of solid-state batteries is inefficient at all stages, making it difficult to achieve continuous production.
The positive electrode and negative electrode electrolyte powder are crushed and mixed by acoustic resonance method to form a coated modified positive electrode and a modified negative electrode, and a separator is prepared by acoustic resonance method to combine it into a full solid state battery.
The coating time is greatly reduced, the coating effect is enhanced, the specific capacity of the electrode is improved, the process time is shortened from several hours to several minutes, and the production efficiency is improved.
Smart Images

Figure CN119650876A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to an all-solid-state battery and a preparation method thereof. Background Art
[0002] As a simple and efficient energy storage system, lithium-ion batteries are highly valued at all levels of modern energy technology development. However, the organic electrolytes of traditional liquid batteries are toxic and flammable during use. Lithium dendrites can easily penetrate the diaphragm and cause internal short circuits in the battery, making liquid batteries flammable and explosive. Therefore, replacing the electrolytes and diaphragms in traditional lithium-ion batteries with solid electrolytes and developing safe, high-performance and low-cost all-solid-state batteries has become a major challenge in the world's energy field today.
[0003] For sulfide solid electrolytes or halide solid electrolytes, the preparation process usually requires processes such as crushing, coating, mixing and bonding; for the crushing process, the solid electrolyte is generally large particles of micron size after synthesis, but the large particle size makes it difficult to prepare a solid electrolyte membrane, and is not conducive to the improvement of volume energy density, so crushing is required. The traditional method is to use ball milling for secondary particle refinement, but the overall process is relatively cumbersome. In addition to the requirements for ball-to-material ratio and rotation speed, it also requires a long time of ball milling, which is not conducive to continuous production. Solid electrolyte coating is a method of coating solid electrolyte materials on the surface of electrode materials (such as positive electrode materials), which can reduce side reactions and enhance the stability and cycle performance of electrode materials. However, physical or chemical means are often required for deposition and coating during the coating process. The process is relatively cumbersome and has a high demand for coating materials, which is not conducive to efficient and continuous production. In addition, the mixing of positive and negative electrodes needs to take into account performance and efficiency. The traditional process often uses ball milling for mixing. Although the dispersion is well guaranteed, it greatly affects the production efficiency of solid-state batteries and is difficult to produce continuously. On the other hand, during the diaphragm production process, the dispersion process of the binder will affect the film-making efficiency, and its dispersion directly affects the battery rate performance. However, the binder is difficult to disperse quickly during the film-making process, affecting the continuous production process, and excessive use of the binder will affect the performance of the diaphragm.
[0004] Therefore, in the production process of solid-state batteries, due to process limitations, the current production efficiency of solid-state electrolytes is relatively low, making it difficult to achieve continuous operation and production of solid-state batteries. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide an all-solid-state battery and a method for preparing the same, so as to solve the problem in the prior art that the production process of solid-state batteries is inefficient at all stages and it is difficult to achieve continuous production.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention discloses a method for preparing an all-solid-state battery, comprising the following steps: S1, by using the acoustic resonance method to break up the positive and negative electrolytes, respectively, to obtain M 1 Positive electrode electrolyte powder and M 2 The negative electrode electrolyte powder has a particle size of M 1 and M 2 are all natural numbers ≥ 2; the positive electrode electrolyte is a halide, and the negative electrode electrolyte is a sulfide; S2, Mixed N 1 The cathode electrolyte powder of different particle sizes is used to form a cathode solid electrolyte by acoustic resonance method, and mixed with N 2 The negative electrode electrolyte powder of various particle sizes is used to form a negative electrode solid electrolyte by acoustic resonance method. 1 and N 2 All are natural numbers ≥ 2; S3, mixing the positive electrode solid electrolyte and the positive electrode material by an acoustic resonance method to form a modified positive electrode in a coated form, and mixing the negative electrode solid electrolyte and the negative electrode material by an acoustic resonance method to form a modified negative electrode in a coated form; S4, after combining the modified positive electrode, separator and modified negative electrode, an all-solid-state battery is obtained.
[0007] Preferably, in S3, the negative electrode material is nano-silicon, micron silicon or lithium negative electrode, and the positive electrode material is a ternary nickel-based material or nickel-cobalt-manganese oxide, which means that the method can be applied to the most common negative electrode materials and positive electrode materials on the market.
[0008] Preferably, in S2, the N 1 The positive electrode electrolyte powder of the graded particle size and the N 2 The negative electrode electrolyte powders of various particle sizes all meet the particle grading requirements. During the mixing process, the particle grading scheme can improve the compaction density of the electrolyte.
[0009] Preferably, the modified positive electrode in S3 is composed of a coating material and a coated material, when the coating material is a positive electrode solid electrolyte, the coated material is a positive electrode material; when the coating material is a positive electrode material, the coated material is a positive electrode solid electrolyte; The modified negative electrode is composed of a coating material and a coated material. When the coating material is a negative electrode solid electrolyte, the coated material is a negative electrode material; when the coating material is a negative electrode material, the coated material is a negative electrode solid electrolyte. The selection of the coating material and the coated material can be adjusted according to actual conditions.
[0010] Preferably, the coating material and the coated material are both granular, and the particle size of the granular coated material is more than one hundred times the particle size of the granular coating material. Differentiating the particle sizes of the coating material and the coated material can complete the coating process and ensure the coating effect.
[0011] Preferably, in S1, S2 and S3, the parameters controlled by the acoustic resonance method include frequency, acceleration and time. By adjusting the parameters such as time, frequency and acceleration of the acoustic resonance method, the crushing and mixing of the positive and negative electrolytes of the solid-state battery, the coating of the size of the positive and negative electrodes of the battery, and other processes can be achieved, making the method suitable for the whole process of preparing all-solid-state batteries.
[0012] Preferably, in S4, the diaphragm is a double-layer diaphragm, and the double-layer diaphragm is a halide diaphragm and a sulfide diaphragm, respectively, and the halide diaphragm and the sulfide diaphragm are both obtained by an acoustic resonance method. The preparation efficiency of the diaphragm can be improved by preparing the halide diaphragm and the sulfide diaphragm by the acoustic resonance method.
[0013] Preferably, the specific process of preparing the diaphragm is as follows: a sulfide agglomerate mixture is obtained by mixing the negative electrode solid electrolyte and the binder by an acoustic resonance method, and the sulfide agglomerate mixture is extruded into a film to obtain a sulfide diaphragm; a halide agglomerate mixture is obtained by mixing the positive electrode solid electrolyte and the binder by an acoustic resonance method, and the halide agglomerate mixture is extruded into a film to obtain a halide diaphragm; a sulfide diaphragm and a halide diaphragm are co-extruded and compounded to obtain a double-layer diaphragm. In the process of preparing the diaphragm, the binder and the solid electrolyte material are formed into a mass mixture by an acoustic resonance method, so that the binder is dispersed quickly and evenly, thereby reducing the amount of the binder, and thus improving the performance of the diaphragm.
[0014] Preferably, in the sulfide agglomerated mixture, the mass of the binder is 0.5%-3% of the mass of the negative electrode solid electrolyte; in the halide agglomerated mixture, the mass of the binder is 0.5%-3% of the mass of the positive electrode solid electrolyte. In the process of preparing the diaphragm by the acoustic resonance method of the present invention, the amount of binder added to the diaphragm is lower than the conventional amount of binder of about 5%.
[0015] An all-solid-state battery prepared by any one of the above preparation methods comprises a modified positive electrode, a separator and a modified negative electrode.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing an all-solid-state battery. The all-solid-state battery includes a crushing and mixing process of the electrolyte in the process of preparing a positive electrode solid electrolyte and a negative electrode solid electrolyte, and then forms a coated modified positive electrode and a modified negative electrode by an acoustic resonance method. The invention evenly mixes electrolyte powders of different particle sizes by the acoustic resonance method, and can prepare a large amount of electrolyte at one time. Furthermore, the modified positive electrode and the modified negative electrode prepared by the acoustic resonance method have a complete structure and a uniform particle size, and can greatly reduce the coating time and enhance the coating effect compared with other methods. The electrode finally obtained has a better specific capacity than direct stirring. The method of the invention uses the acoustic resonance method in each step of the process of preparing the modified positive electrode and the modified negative electrode of the all-solid-state battery. Compared with the existing ball milling process, the process time is reduced from several hours to several minutes, and the crushing efficiency is greatly improved. Compared with the ball milling process, the efficiency is higher and the stability is better.
[0017] The present invention also discloses an all-solid-state battery, in which the modified positive electrode, modified negative electrode or diaphragm are prepared using an acoustic resonance method, and the solid electrolyte used in the preparation process is a solid electrolyte prepared by the above-mentioned acoustic resonance method, so that the uniformity of the positive and negative electrode materials and the diaphragm is better. The solid-state battery performance data obtained by this method has obvious advantages over traditional ball milling and other methods, and exhibits good performance while improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a comparison of the before and after the negative electrode electrolyte is broken by the acoustic resonance method; Among them, (a) is a schematic diagram of the raw material; (b) is a result diagram after acoustic resonance; Figure 2 Nano-Si coated Li 5.5 PS 4.5 SEM (scanning electron microscope) schematic diagram of the Cl negative electrode solid electrolyte; Figure 3 It is a comparison chart of the constant current charge and discharge performance test results of Example 1 and Comparative Example 1; Figure 4 The first-cycle voltage and capacity test results of Example 2, Comparative Example 2 and Comparative Example 3 are shown; Figure 5 The test results of the charge and discharge capacity of the half-cells obtained in Example 2 and Comparative Example 3 are shown; Figure 6 This is a comparison chart of all-solid-state battery test cycles of Example 4 and Comparative Example 4; Figure 7 This is a test diagram of the charge and discharge performance of the all-solid-state battery of Example 5; Figure 8This is a test diagram of the charge and discharge performance of the all-solid-state battery of Example 6; Fig. 9 This is a test diagram of the charge and discharge performance of the all-solid-state battery of Example 7; Fig.10 This is a test diagram of the charge and discharge performance of the all-solid-state battery of Example 8. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0021] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0022] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0023] The core idea of the present invention is to prepare positive electrode electrolyte and negative electrode electrolyte by acoustic resonance method, further to quickly prepare modified positive electrode, modified negative electrode and separator by acoustic resonance method, and further to prepare all-solid-state battery, so that all-solid-state battery can be prepared on a large scale and efficiently.
[0024] The first aspect of the present invention discloses a method for preparing an all-solid-state battery, comprising the following steps: S1, by using the acoustic resonance method to break up the positive and negative electrolytes, respectively, to obtain M 1Positive electrode electrolyte powder and M 2 The negative electrode electrolyte powder has a particle size of M 1 and M 2 are all natural numbers ≥ 2; the positive electrode electrolyte is a halide, and the negative electrode electrolyte is a sulfide; S2, Mixed N 1 The cathode electrolyte powder of different particle sizes is used to form a cathode solid electrolyte by acoustic resonance method, and mixed with N 2 The negative electrode electrolyte powder of various particle sizes is used to form a negative electrode solid electrolyte by acoustic resonance method. 1 and N 2 All are natural numbers ≥ 2; S3, mixing the positive electrode solid electrolyte and the positive electrode material by an acoustic resonance method to form a modified positive electrode in a coated form, and mixing the negative electrode solid electrolyte and the negative electrode material by an acoustic resonance method to form a modified negative electrode in a coated form; S4, after combining the modified positive electrode, separator and modified negative electrode, an all-solid-state battery is obtained.
[0025] Acoustic resonance refers to the process in which a system (such as a cavity) vibrates at a certain frequency and amplitude when it is subjected to external sound waves. If the frequency of the external sound wave is close to or equal to the natural frequency of the system, the vibration amplitude of the system will increase sharply and resonance will occur. This is because the external sound wave provides additional energy to the system, enabling it to overcome the internal damping force and vibrate with a larger amplitude. The acoustic resonance method used in the present invention is to use acoustic resonance equipment to perform processes such as material crushing, mixing, coating and dispersion.
[0026] In some embodiments of the present invention, in S1, the specific halide can be Li 3 InCl 6 , Li 2 ZrCl 6 , Li 3 TaCl 6 , Li 3 NbCl 6 , Li 3 AlCl 6 , Li 3 GaCl 6 , Li 2+x In x Zr 1-x Cl 6 Oxyhalides (x ranges from 0 to 1), LiNbOCl, LiTaOCl 4 , Li 2 ZrO 4 or LiNbOCl 4 Any one or more of the .
[0027] Sulfide can be Li 6 PS 5 Cl, Li 5.5 PS 4.5 Cl, Li 5.5 PS 5 Cl, Li 5.4 PS 5 Cl, Li 5.3 PS 5 Cl or Li 5.5 PS 5 Cl y Br 1-y (y ranges from 0 to 1)
[0028] It can be seen that the method for preparing the electrolyte of the present invention is applicable to common halide solid electrolytes and sulfide solid electrolytes, which makes the method have great universality and promotion.
[0029] It should be understood that in S1, after the positive electrode electrolyte and the negative electrode electrolyte are crushed by the acoustic resonance method, they are in powder form, and M is obtained after screening. 1 Positive electrode electrolyte powder and M 2 Negative electrolyte powder of graded particle size, M 1 and M 2 The specific value of is determined according to the actual situation. This step is a physical refinement process, which makes the electrolyte particles smaller and forms electrolyte powders of different particle sizes.
[0030] Furthermore, in S2, in the above M 1 Find the N that meets the particle grading requirements from the positive electrolyte powder of various particle sizes. 1 The positive electrode electrolyte powder of the particle size of each grade is used to form a positive electrode solid electrolyte by an acoustic resonance method; 2 Find the N that meets the particle grading requirements from the negative electrode electrolyte powder of various particle sizes. 2 The negative electrode electrolyte powder of different particle sizes is used to form a negative electrode solid electrolyte through the acoustic resonance method. 1 Less than M 1 , N 2 Less than M 2 . In this step, particle grading can improve the compaction density of the electrolyte. Solid electrolyte particles of different target sizes have different grading requirements to achieve the maximum compaction density. Through particle grading, lithium dendrite growth can be reduced while taking into account high ionic conductivity. In the mixing process, electrolyte powders of different particle sizes are mixed and used to achieve the highest density to obtain a positive electrode solid electrolyte or a negative electrode solid electrolyte.
[0031] In some embodiments of the present invention, the specific process of crushing in S1 is: first, zirconia beads accounting for 25% of the volume of the container are added to the acoustic resonance device, and the positive electrode electrolyte or negative electrode electrolyte to be crushed is continuously filled into the acoustic resonance container of the acoustic resonance device until the volume filling ratio set by the acoustic resonance container is reached, and the positive electrode electrolyte or negative electrode electrolyte is fixed in the acoustic resonance device, and resonant crushing is performed according to the set frequency. The positive electrode electrolyte or negative electrode electrolyte is crushed into electrolyte powders of multiple particle sizes, and M is obtained by sieving. 1 Positive electrode electrolyte powder or M 2 Negative electrode electrolyte powder with different particle sizes.
[0032] It should be understood that the crushing process of S1 has different frequencies and accelerations for different acoustic resonance devices and different particle size requirements, so that the particle size of the electrolyte powder obtained can meet the requirements. In some specific embodiments, the crushing process is to adjust the acceleration to 100g at a frequency of 60Hz and maintain it for 10min-50min, where Hz is the abbreviation of the frequency unit Hertz, g is the unit of gravity acceleration, 1g=9.8m / s²; min represents minutes, which is the abbreviation of minutes.
[0033] In some embodiments of the present invention, in the mixing process of S2, different equipment and different particle size grades require different frequencies, times and accelerations. In a specific embodiment, the mixing process is adjusted to 60g-100g at a frequency of 30Hz-70Hz and maintained for 3min-10min; exemplarily, the mixing frequency can be 30Hz, 40Hz, 50Hz, 60Hz or 70Hz, exemplarily, the acceleration can be 60g, 70g, 80g, 90g or 100g, and exemplarily, the holding time after reaching the target acceleration can be 3min, 5min, 8min or 10min.
[0034] In some embodiments, the mixing process of S2 can also be mixed in stages, such as mixing for 3 minutes each time, mixing 5 times, and mixing for a total of 15 minutes.
[0035] In a specific embodiment, in S2, positive electrode electrolyte powder or negative electrode electrolyte powder accounting for 90% of the volume of the acoustic resonance container is finally added to the acoustic resonance device, fixed in the acoustic resonance device, and vibration mixing is started to obtain a positive electrode solid electrolyte or a negative electrode solid electrolyte.
[0036] In some embodiments of the present invention, in S3, the modified positive electrode and the modified negative electrode are both composed of a coating material and a coated material, and the particle size of the coating material is smaller than that of the coated material, so that the two types of materials can be agglomerated and adsorbed. For the modified positive electrode, which of the positive electrode solid electrolyte and the positive electrode material is used as the coating material and which is used as the coated material is determined according to demand; for the modified negative electrode, which of the negative electrode solid electrolyte and the negative electrode material is used as the coating material and which is used as the coated material is determined according to demand; during the coating process, the coating material and the coated material are placed in an acoustic resonance device according to a set ratio, and a modified positive electrode and a modified negative electrode in a coated form are formed by an acoustic resonance method. This process is a physical adsorption process. When the coating material and the coated material are at the nanometer and micrometer levels, the surface adsorption effect is strong, and they will spontaneously agglomerate and adsorb to form a coated form.
[0037] The amount of coating material and coated material added during the coating process is related to the mass, volume and specific surface area of the modified positive electrode or modified negative electrode that is finally formed in a coated form. The basic requirement is that the coating material completely wraps the coated material, and the specific thickness is adjusted according to actual conditions.
[0038] The modified positive electrode and the modified negative electrode prepared by the method of the present invention are both core-shell structures, wherein the core is the coating material, the shell is composed of granular coating material, and the granular coating material is attached to the coating material.
[0039] In some preferred embodiments, the particle size of the coated material is more than one hundred times the particle size of the coating material to ensure the coating effect.
[0040] In some specific embodiments, the positive electrode electrolyte is a halide, and the corresponding positive electrode material is a ternary nickel-based material or nickel-cobalt-manganese oxide, etc.; the negative electrode electrolyte is a sulfide, and the corresponding negative electrode material is micron silicon, nano silicon or lithium negative electrode.
[0041] In some specific embodiments, for the modified negative electrode in the form of coating that needs to be able to control the volume expansion of the negative electrode, the coating material is selected as micron Si, and the coated material is selected as sulfide 651 electrolyte, and the coated material particles are about 100 times the size of the coating material. If the direction of enhancing ion conduction is selected, a larger micron Si and a sulfide electrolyte with a smaller particle size can be selected. In this case, the micron Si is the coated material, and the sulfide electrolyte is the coating material to prepare a modified negative electrode.
[0042] Sulfide 651 electrolytes are mainly sulfides, such as Li 6 PS 5 Cl, Li 10 G 2 S 12 , Li 5.5 PS 5 Cl1.5 or Li 5.5 PS 5 C l0.75 Br 0.75 .
[0043] In a specific embodiment, when preparing the modified positive electrode material, the coating material can be lithium niobate, and the coated material can be nickel cobalt manganese oxide.
[0044] In some specific embodiments, during the coating process of S3, different equipment and different particle size grades require different frequencies, times and accelerations. The process parameters of the coating process are: the acceleration is adjusted to 80g-90g at a frequency of 30Hz-80Hz and maintained for 5min-15min. Preferably, the frequency range is 55Hz-60Hz; exemplarily, the frequency can be 30Hz, 40Hz, 50Hz, 55Hz or 60Hz; exemplarily, the acceleration is 80g, 85g or 90g, and exemplarily, the holding time is 5min, 10min or 15min.
[0045] In some embodiments of the present invention, when preparing a modified positive electrode, in addition to the coating material and the coated material, a conductive agent is also added, and the process of adding the conductive agent can be a one-step method or a two-step method. The one-step method is to directly mix the positive electrode solid electrolyte, the positive electrode material and the conductive agent and then prepare the modified positive electrode by an acoustic resonance method. The two-step method is to first mix the positive electrode solid electrolyte and the positive electrode material by an acoustic resonance method to obtain a coated positive electrode, and then mix the coated positive electrode and the conductive agent by an acoustic resonance method to obtain the final modified positive electrode. In the modified positive electrode to which a conductive agent is added, the coated positive electrode is composited on the conductive agent. It should be noted that when the one-step method is used to prepare the modified positive electrode to which a conductive agent is added, the frequency and acceleration are larger than the above-mentioned parameters, providing more energy for the acoustic resonance method.
[0046] The specific conductive agent can be Ketjen black, VGCF (Vapor Grown Carbon Fibers), super-P (small particle conductive carbon black) or single-walled carbon nanotube.
[0047] In some embodiments of the present invention, the diaphragm can also be prepared by an acoustic resonance method, and the diaphragm includes two layers of a halide diaphragm and a sulfide diaphragm pasted together, which is a double-layer diaphragm. The specific preparation process of the diaphragm is to first prepare the halide diaphragm and the sulfide diaphragm separately, and then directly compound the two diaphragms by rolling. Since there is a certain binder inside the diaphragm itself, it is not necessary to add other substances and directly compound. This method can obtain a dense and uniform solid electrolyte membrane by mixing in the case of loose loading, which greatly simplifies the membrane production process.
[0048] In the specific process of preparing the halide diaphragm or the sulfide diaphragm, the corresponding positive electrode solid electrolyte or negative electrode solid electrolyte is mixed with a binder by acoustic resonance method to obtain a halide agglomerate mixture or a sulfide agglomerate mixture, and the agglomerate mixture is rolled to obtain the corresponding diaphragm; in the sulfide agglomerate mixture, the mass of the binder is 0.5%-3% of the mass of the negative electrode solid electrolyte; in the halide agglomerate mixture, the mass of the binder is 0.5%-3% of the mass of the positive electrode solid electrolyte.
[0049] The thickness of the halide diaphragm or the sulfide diaphragm is in the range of 20 μm to 200 μm.
[0050] In some specific embodiments, in this step, the binder and the solid electrolyte (positive electrode solid electrolyte or negative electrode solid electrolyte) are added to the acoustic resonance device in amount and mixed by the acoustic resonance method. The frequency during the mixing process is 40 Hz-80 Hz, preferably 55 Hz-60 Hz, the acceleration is 60 g-100 g, preferably 60 g-90 g, and the mixing time is 3 min-20 min, preferably 5 min-10 min.
[0051] In a specific embodiment, the binder is tetrafluoroethylene (PTFE, also known as Teflon), and the acceleration is adjusted to 60g at a frequency of 60 Hz for 10 minutes. During this process, tetrafluoroethylene stretches from agglomeration to fiber state, which can better combine with the solid electrolyte.
[0052] In some embodiments of the present invention, in the above-mentioned S1-S4, the filler ratio in the acoustic resonance device is 50%-100%, preferably 80%-90%.
[0053] Based on the above preparation method, the present invention also discloses an all-solid-state battery, which includes a modified positive electrode, a modified negative electrode and a separator, wherein the modified positive electrode and the modified negative electrode are both prepared by the above-mentioned acoustic resonance method.
[0054] As a preferred solution, the modified positive electrode, modified negative electrode and diaphragm in the all-solid-state battery are all prepared by an acoustic resonance method based on the above-mentioned solid electrolyte. The diaphragm is a double-layer diaphragm, the sulfide diaphragm close to the modified negative electrode and the halide diaphragm close to the modified positive electrode.
[0055] It can be seen from the above process that the present invention can realize the processes of crushing, mixing, coating, etc. through the acoustic resonance equipment. The specific effect that can be realized depends on the energy of the input acoustic resonance. Specifically, the frequency, time and acceleration need to be controlled during the acoustic resonance process. When the energy is large and there is shear force, particle crushing can be achieved, and generally only single particle crushing is targeted. When the energy is small and there are more types of particles, the particle size distribution is similar or not much different, then the particles tend to be evenly distributed under the action of acoustic resonance, and when the energy is small and there are more than two kinds of particle sizes with a large difference, a coating material is formed. Generally speaking, nanometers can achieve uniform coating of micron particles. When forming a diaphragm, the formation of a mass-like mixture also belongs to mixing, because PTFE is fibrous, but often agglomerates into particles at room temperature, and acoustic resonance can unfold these particles, so it is equivalent to evenly dispersing the fibers, and after completion, the mass-like mixture is rolled to obtain a diaphragm. The method of the present invention can quickly and efficiently use electrolytes to coat electrode materials, and can quickly prepare diaphragms through a small amount of binders, so that solid-state batteries can be produced efficiently on a large scale.
[0056] The following is further described in conjunction with specific embodiments.
[0057] Example 1 This embodiment prepares a modified negative electrode and verifies the performance of the modified negative electrode, specifically comprising the following steps: (1) Add 10 g of 8 mm φ zirconium oxide beads to a 15 mL acoustic resonance device. 5.5 PS 4.5 The electrolyte of LiCl (LPSC for short) was filled to 80% of the volume of the acoustic resonance container and fixed in the acoustic resonance device. At a frequency of 60Hz, the acceleration was adjusted to 100g and the intensity was maintained at 30% for 10min to obtain the negative electrode electrolyte powder. 5.5 PS 4.5 The Cl electrolyte particles are broken and refined, see Figure 1 , (a) is a schematic diagram of the raw materials, (b) is the result obtained after 10 minutes of acoustic resonance, Figure 1 In the figure, SED (Secondary Electron Detector), kV (Kilovolt) is the voltage unit, WD is the working distance, mm is the length unit, μm is the length unit, and FOV (Field of View) is the field of view. Under the same magnification, it can be clearly observed that the electrolyte particles are broken and refined. The broken and refined electrolyte particles are sieved according to the set particle size to obtain three grades of negative electrode electrolyte powder.
[0058] (2) Add 5g of 10μm-15μm, 3g of 3μm-5μm, and 2g of 0.8μm-1.2μm Li into the acoustic resonance device. 5.5 PS 4.5 The total volume of the Cl negative electrode electrolyte powder reaches 90% of the acoustic resonance device, which is fixed in the acoustic resonance device and the acceleration is adjusted to 80g at a frequency of 60Hz for 5min to obtain a dense Li 5.5 PS 4.5 Cl negative electrode solid electrolyte. From the results, it is found that Li 5.5 PS 4.5 The powder of Cl negative electrode solid electrolyte was relatively loose before acoustic resonance grading, but became denser after acoustic resonance grading.
[0059] (3) 1g of 50nm silicon powder was used as negative electrode material and 1g of Li obtained in step (2) was added. 5.5 PS 4.5 The Cl negative electrode solid electrolyte was added to the acoustic resonance device, and the acceleration was adjusted to 80g at a frequency of 60Hz for 5min to obtain nano-silicon-coated Li 5.5 PS 4.5 Cl modified negative electrode, such as Figure 2 The coating results shown in the figure show that the overall coating effect is good. 5.5 PS 4.5 The Cl negative electrode solid electrolyte is completely covered by silicon powder and is nearly spherical. In the figure, k in 22k represents thousand times, and ×22k represents 22,000 times magnification.
[0060] (4) The modified negative electrode material and lithium indium are combined into a half-cell for constant current charge and discharge performance testing.
[0061] Comparative Example 1 Micron silicon and lithium indium are combined into a half-cell for constant current charge and discharge performance testing.
[0062] The test results of Example 1 and Comparative Example 1 are compared. Figure 3 It can be seen that the half-cell rate performance and cycle stability after coating can be stably improved. Figure 3 In the figure, mAh / g stands for energy density, which is the unit of charge specific capacity. mAh stands for milliampere-hour, and g stands for the weight of the battery.
[0063] Example 2 This embodiment prepares a modified positive electrode and verifies the performance of the modified positive electrode, specifically comprising the following steps: (1) Add 10 g of 8 mm φ zirconium oxide beads to a 15 mL acoustic resonance device. 3 InCl 6(abbreviated as LIC) electrolyte is filled to 80% of the volume of the acoustic resonance container, fixed in the acoustic resonance device, and the acceleration is adjusted to 100g at a frequency of 60Hz, and the intensity is maintained at 30% for 10 minutes. 3 InCl 6 The electrolyte particles are crushed and refined to obtain positive electrode electrolyte powder.
[0064] (2) Add 5g of 10μm-15μm, 3g of 3μm-5μm, and 2g of 0.8μm-1.2μm Li into the acoustic resonance device. 3 InCl 6 The positive electrode electrolyte powder, whose total volume reaches 90% of the acoustic resonance container, is fixed in the acoustic resonance device and the acceleration is adjusted to 80g at a frequency of 60Hz for 5min to obtain a dense Li 3 InCl 6 Positive solid electrolyte.
[0065] (3) 1.4 g of Ni88 positive electrode material (LiNi 0.88 Co 0.09 Mn 0.03 O 2 ), 0.1g of conductive agent VGCF and 0.5g of Li 3 InCl 6 The positive electrode solid electrolyte is added into the acoustic resonance device, and the acceleration is adjusted to 90g at a frequency of 60Hz and maintained for 15 minutes. The strength requirement during the acoustic resonance device process is >20%, and a modified positive electrode is obtained.
[0066] (4) The modified positive electrode battery material obtained in step (3) and lithium indium are combined into a half-cell to perform a voltage capacity test.
[0067] Comparative Example 2 The Ni88 positive electrode material and lithium indium were combined into a half-cell for voltage and capacity testing.
[0068] Comparative Example 3 1.4g of Ni88 positive electrode material (5μm-10μm) and 0.5g of Li 3 InCl 6 The electrolyte powder (0.5 μm-1 μm) was directly ball-milled at a speed of 300 rpm for 15 min to obtain a positive electrode, which was then combined with lithium indium to form a half-cell for voltage and capacity testing.
[0069] The first-cycle voltage and capacity test results of Example 2, Comparative Example 2 and Comparative Example 3 are compared. Figure 4 , Figure 4V represents voltage. It can be seen from the figure that the test results of Example 2 and Comparative Example 3 are better than the positive electrode without LIC coating in Comparative Example 2, and the modified positive electrode obtained in Example 2 has the best test result, and the efficiency of the acoustic resonance method is higher.
[0070] The half-cells obtained in Example 2 and Comparative Example 3 were tested for charge and discharge capacity. The test results are as follows: Figure 5 As shown, it can be seen that after multiple cycles, the charge and discharge specific capacity of the modified positive electrode prepared by the acoustic resonance method is higher than that of the positive electrode prepared by the ball milling method.
[0071] Example 3 Li prepared in step (2) of Example 1 5.5 PS 4.5 Cl negative electrode solid electrolyte to prepare sulfide diaphragm, the specific process is: 0.005g tetrafluoroethylene and 1g Li 5.5 PS 4.5 The Cl negative electrode solid electrolyte was placed in a 15 mL acoustic resonance device, 10 g of φ8 mm zirconium oxide ball milling beads were added, and the acceleration was adjusted to 60 g at a frequency of 60 Hz for 10 min to obtain a sulfide agglomerate mixture, and the sulfide agglomerate mixture was roller-pressed to obtain a complete sulfide diaphragm dispersed with tetrafluoroethylene.
[0072] Li prepared in step (2) of Example 2 3 InCl 6 The positive electrode solid electrolyte is used to make the halide diaphragm. The specific process is: 0.005g of tetrafluoroethylene and 1g of Li 3 InCl 6 The positive electrode solid electrolyte was placed in a 15 mL acoustic resonance device, 10 g of φ8 mm zirconium oxide ball milling beads were added, and the acceleration was adjusted to 60 g at a frequency of 60 Hz for 10 min to obtain a halide agglomerate mixture, and the halide agglomerate mixture was subjected to roller pressing to obtain a complete halide diaphragm dispersed with tetrafluoroethylene.
[0073] The sulfide membrane and the halide membrane are directly compounded and then subjected to roller pressing to obtain a final membrane. The double-layer membrane prepared in this embodiment is dense and uniform.
[0074] Example 4 The modified negative electrode obtained in Example 1, the modified positive electrode obtained in Example 2, and the diaphragm obtained in Example 3 are assembled, wherein the sulfide diaphragm is on one side of the modified negative electrode and the halide diaphragm is on one side of the modified positive electrode, to obtain an all-solid-state battery.
[0075] Comparative Example 4 1.4 g of Ni88 positive electrode material, 0.1 g of conductive agent VGCF, and 0.5 g of LIC were added to the ball mill and milled at 300 rpm for 6 h to obtain the positive electrode of the battery. Micronized Si was used as the negative electrode and conventional LIC / Li 5.5 PS 4.5 Cl is used as a separator to prepare an all-solid-state battery. Here, the conventional LIC / Li 5.5 PS 4.5 The Cl membrane refers to a membrane that is not prepared by the acoustic resonance method.
[0076] The all-solid-state battery obtained in Example 4 was subjected to charge and discharge cycles, and the all-solid-state battery obtained in Comparative Example 4 was subjected to charge and discharge cycles. The comparison results are as follows: Figure 6 As shown, although the comparative example 4 has a higher discharge capacity in the first cycle, the capacity retention rate and stability in the subsequent cycles are not as good as those of the example 4 of the acoustic resonance method, and the acoustic resonance method greatly reduces the mixing time. The electrode material prepared by the acoustic resonance method has a uniform composition, so that the final all-solid-state battery has good electrochemical properties. The electrode material finally obtained has a better specific capacity than direct ball milling. Compared with the battery positive electrode prepared by ordinary powdering, the contact between the positive electrode particles and the electrolyte particles in the modified positive electrode will be better, which is conducive to the release of the battery specific capacity.
[0077] Example 5 (1) Add 10 g of 8 mm φ zirconium oxide beads to a 15 mL acoustic resonance device. 6 PS 5 The Cl electrolyte was filled to 50% of the volume of the acoustic resonance container and fixed in the acoustic resonance device. At a frequency of 60 Hz, the acceleration was adjusted to 100 g and the intensity was maintained at 30% for 10 minutes. 6 PS 5 The Cl electrolyte particles are crushed and refined to obtain negative electrode electrolyte powder.
[0078] (2) Add 5g of 10μm-15μm, 3g of 3μm-5μm, and 2g of 0.8μm-1.2μm Li into the acoustic resonance device. 6 PS 5 The total volume of the Cl negative electrode electrolyte powder reaches 90% of the acoustic resonance container, which is fixed in the acoustic resonance device and the acceleration is adjusted to 60g at a frequency of 55Hz for 10min to obtain a dense Li 6 PS 5 Cl anode solid electrolyte.
[0079] (3) 1g of 50nm silicon powder is used as the negative electrode material and 1g of Li obtained in step (2) 6 PS 5The Cl negative electrode solid electrolyte was added into an acoustic resonance device, and the acceleration was adjusted to 80 g at a frequency of 55 Hz and maintained for 5 min to obtain a modified negative electrode.
[0080] (4) Add 10 g of 8 mm φ zirconium oxide beads to a 15 mL acoustic resonance device. 3 InCl 6 The electrolyte is filled to 50% of the volume of the acoustic resonance container and fixed in the acoustic resonance container. At a frequency of 60 Hz, the acceleration is adjusted to 100 g and the intensity is maintained at 30% for 10 minutes. 3 InCl 6 The electrolyte particles are crushed and refined to obtain positive electrode electrolyte powder.
[0081] (5) Add 5g of 10μm-15μm, 3g of 3μm-5μm, and 2g of 0.8μm-1.2μm Li into the acoustic resonance device. 3 InCl 6 The positive electrode electrolyte powder, whose total volume reaches 90% of the acoustic resonance device, is fixed in the acoustic resonance device and the acceleration is adjusted to 60g at a frequency of 55Hz for 10min to obtain a dense Li 3 InCl 6 Positive solid electrolyte.
[0082] (6) 1.4 g of Ni88 positive electrode material and 0.5 g of Li 3 InCl 6 The positive electrode solid-state electrolysis was added to the acoustic resonance equipment, the acceleration was adjusted to 80g at a frequency of 55 Hz and maintained for 5 minutes to obtain a coated positive electrode, the coated positive electrode was mixed with 0.1g of conductive agent VGCF by an acoustic resonance method, the acceleration was adjusted to 80g at a frequency of 55 Hz and maintained for 5 minutes to obtain a modified positive electrode.
[0083] (7) Prepare Li from step (2) 6 PS 5 Cl negative electrode solid electrolyte is used to prepare sulfide diaphragm. The specific process is: 0.005g tetrafluoroethylene and 1g Li obtained in step (2) are mixed. 6 PS 5 The Cl negative electrode solid electrolyte was placed in a 15 mL acoustic resonance device, 10 g of φ8 mm zirconium oxide ball milling beads were added, and the acceleration was adjusted to 80 g at a frequency of 30 Hz for 20 min to obtain a mass mixture, which was then rolled to obtain a complete sulfide diaphragm dispersed with tetrafluoroethylene.
[0084] Step (5) to obtain Li 3 InCl 6The positive electrode solid electrolyte is used to prepare the halide diaphragm. The specific process is: 0.005g of tetrafluoroethylene and 1g of Li obtained in step (5) are mixed. 3 InCl 6 The positive electrode solid electrolyte was placed in a 15 mL acoustic resonance device, 10 g of φ8 mm zirconium oxide ball milling beads were added, and the acceleration was adjusted to 80 g at a frequency of 30 Hz for 20 min to obtain a mass mixture, which was then rolled to obtain a complete halide diaphragm dispersed with tetrafluoroethylene.
[0085] The halide diaphragm and the sulfide diaphragm are rolled and extruded to obtain a final composite diaphragm.
[0086] (8) Assembling the modified negative electrode obtained in step (3), the modified positive electrode obtained in step (6) and the separator obtained in step (8), wherein the sulfide separator is on one side of the modified negative electrode and the halide separator is on one side of the modified positive electrode, to obtain an all-solid-state battery.
[0087] The charge and discharge performance of the all-solid-state battery prepared in Example 5 was tested. Figure 7 It can be seen that the rate performance is good and the long cycle stability at 0.5C is good. 0.5C refers to the capacity factor of the battery energy storage system, which describes the relationship between the capacity of the battery energy storage system and its discharge depth. For example, if the rated capacity of a battery is 200Ah, then 0.5C is equivalent to a charging or discharging rate of 100A, that is, the battery can be fully charged or fully discharged in 2 hours, and C is the definition of the current size.
[0088] The parameters and test performance of Examples 6 to 8 are described below by means of diagrams. The preparation processes of Examples 6 to 8 are the same as those of Example 5 except for the changes in parameters.
[0089] Table 1 Experimental parameters of Example 6-Example 8
[0090] Combination Figure 8-Figure 10 It can be seen that the all-solid-state battery prepared in Example 6, at 0.5C conditions, when the capacity is 100mAh / g, after 200 cycles, the specific capacity can still be maintained at 99%. The all-solid-state battery prepared in Example 7, at 0.5C conditions, when the capacity is 143mAh / g, after 200 cycles, the specific capacity can still be maintained at 70%. The all-solid-state battery prepared in Example 7, at 0.5C conditions, when the capacity is 123mAh / g, after 200 cycles, the specific capacity can still be maintained at 84%. This shows that the all-solid-state batteries prepared in these embodiments have good cycle stability.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an all-solid-state battery, characterized in that: The following steps are involved: S1, crushing the positive electrode electrolyte and the negative electrode electrolyte respectively by an acoustic resonance method to obtain a positive electrode electrolyte powder with a particle size of M1 and a negative electrode electrolyte powder with a particle size of M2, wherein both M1 and M2 are natural numbers ≥ 2; the positive electrode electrolyte is a halide, and the negative electrode electrolyte is a sulfide; S2, mixing positive electrode electrolyte powders of N1 levels of particle size to form a positive electrode solid electrolyte by an acoustic resonance method, and mixing negative electrode electrolyte powders of N2 levels of particle size to form a negative electrode solid electrolyte by an acoustic resonance method, where N1 and N2 are both natural numbers ≥ 2; S3, mixing the positive electrode solid electrolyte and the positive electrode material by an acoustic resonance method to form a modified positive electrode in a coated form, and mixing the negative electrode solid electrolyte and the negative electrode material by an acoustic resonance method to form a modified negative electrode in a coated form; S4, after combining the modified positive electrode, separator and modified negative electrode, an all-solid-state battery is obtained.
2. The method for preparing an all-solid-state battery according to claim 1, characterized in that: In S3, the negative electrode material is nano-silicon, micro-silicon or lithium negative electrode, and the positive electrode material is ternary nickel-based material or nickel-cobalt-manganese oxide.
3. The method for preparing an all-solid-state battery according to claim 1, characterized in that: In S2, the positive electrode electrolyte powder of the N1 level particle size and the negative electrode electrolyte powder of the N2 level particle size both satisfy the particle grading.
4. The method for preparing an all-solid-state battery according to claim 1, characterized in that: The modified positive electrode described in S3 is composed of a coating material and a coated material. When the coating material is a positive electrode solid electrolyte, the coated material is a positive electrode material; when the coating material is a positive electrode material, the coated material is a positive electrode solid electrolyte; The modified negative electrode is composed of a coating material and a coated material. When the coating material is a negative electrode solid electrolyte, the coated material is a negative electrode material; when the coating material is a negative electrode material, the coated material is a negative electrode solid electrolyte.
5. The method for preparing an all-solid-state battery according to claim 4, characterized in that: The coating material and the coated material are both in granular form, and the particle size of the granular coated material is more than one hundred times the particle size of the granular coating material.
6. The method for preparing an all-solid-state battery according to claim 1, characterized in that: In S1, S2 and S3, the parameters controlled by the acoustic resonance method include frequency, acceleration and time.
7. The method for preparing an all-solid-state battery according to claim 1, characterized in that: In S4, the diaphragm is a double-layer diaphragm, and the double-layer diaphragm is a halide diaphragm and a sulfide diaphragm respectively, and the halide diaphragm and the sulfide diaphragm are both obtained by an acoustic resonance method.
8. The method for preparing an all-solid-state battery according to claim 7, characterized in that: The specific process of preparing the diaphragm is as follows: a sulfide agglomerate mixture is obtained by mixing a negative electrode solid electrolyte and a binder by an acoustic resonance method, and the sulfide agglomerate mixture is extruded into a film to obtain a sulfide diaphragm; a halide agglomerate mixture is obtained by mixing a positive electrode solid electrolyte and a binder by an acoustic resonance method, and the halide agglomerate mixture is extruded into a film to obtain a halide diaphragm; and a sulfide diaphragm and a halide diaphragm are co-extruded and compounded to obtain a double-layer diaphragm.
9. The method for preparing an all-solid-state battery according to claim 8, characterized in that: In the sulfide agglomerated mixture, the mass of the binder is 0.5%-3% of the mass of the negative electrode solid electrolyte; in the halide agglomerated mixture, the mass of the binder is 0.5%-3% of the mass of the positive electrode solid electrolyte.
10. An all-solid-state battery prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It includes a modified positive electrode, a separator and a modified negative electrode.
Citation Information
Patent Citations
High-compaction composite positive electrode material for solid-state battery as well as preparation method and application of high-compaction composite positive electrode material
CN114520317A
High-mechanical-strength coating-layer-containing positive electrode material, preparation method and application thereof
CN114864940A
All-solid-state lithium ion battery and preparation method thereof
CN116314654A
All-solid-state lithium ion battery
CN117154202A
Method for preparing nano-powder coated metal powder by adopting medium-assisted acoustic resonance mixing technology
CN118371719A
Cited By
Multi-component in-situ polymerized gel solid electrolyte as well as preparation method and application thereof
CN120657237A